Clicks or Connections? Examining How Content Marketing and Customer Experience Fuel Repurchase Behavior Among Filipino Consumers - Gonzales, Minard Jr; Martinez, Junna; Limos, Shaniah (Community Development Journal, 2025)
Abstract This community service project addresses the significant challenges faced by digital Small and Medium Enterprise (SME) owners in Davao City, Philippines, primarily digitally literate female entrepreneurs (25–45) using platforms like Shopee and Instagram. The background problem is recurrent erratic turnover and low customer retention, rooted in a crucial empirical knowledge gap that leads to the misallocation of limited marketing budgets. Owners frequently perceive effective digital marketing as prohibitively expensive, resulting in disproportionate and expensive over-investment in reactive Content Marketing (CM) efforts (e.g., boosted posts and micro-influencers) while neglecting the development of essential Customer Experience (CE) infrastructure (e.g., efficient logistics, responsive post-purchase follow-up). The project's core objective was to empirically validate and disseminate actionable, data-driven insights proving the relative impact of CE versus CM on customer loyalty, specifically focusing on increasing Repurchase Intention (RI). The method involved a phased, structured four-week virtual intervention, which included (1) research dissemination, (2) skill-building workshops on CE touchpoint optimization and value-driven CM, (3) provision of practical tool kits like the Post-Purchase Communication Script, and (4) guided mentoring and progress monitoring for implementation. The central result unequivocally confirmed that Customer Experience (CE) is the superior predictor of Repurchase Intention ($β_{CE} = 0.58$), significantly outweighing the impact of the current reactive Content Marketing efforts ($β_{CM} = 0.21$). The intervention successfully drove measurable behavioral shifts, particularly an increased focus on CE audit and optimization metrics, leading to a documented 12% improvement in the average 30-day Repurchase Rate among participating businesses. This project concludes that sustainable and scalable growth for resource-constrained digital SMEs is best achieved by strategically investing in low-cost, high-return service infrastructure over expensive, reactive advertising.Keywords: Customer Experience; Repurchase Intention; Content Marketing; Digital SMEs; Budget Allocation